Evaluación de las competencias en el nivel universitario: Una mirada retrospectiva y actual - Aliaga Murray, Nelly (2011)
The present article presents a summary of the competence approach developments in the Superior Education . First, the determined factors which influenced in the paradigm change for universities since 2000areanalyzed. Then, it developedthe meaningofeducationbasedincompetencesandtheneedofa continuous evaluation which assures the achievement of the competence. lt is emphasized in the conceptual and methodological aspects of the competence evaluation. Likewise, the elements to consider when starting the evaluation actions by competences, as the competence definition process, the elaboration of models, methods, strategies and reliable meansforthe performance evaluation of the professional training, are reviewed.